KEPUTUSAN KOREA SELATAN DALAM MEMILIH INDONESIA SEBAGAI MITRA KERJASAMA PROYEK PENGEMBANGAN PESAWAT TEMPUR MODERN KFX/IFX - Panji Bangun Pratama (HI 15 UMY 410, 2015)
*410 South Korea is a developed country in terms of technology. In terms of military technology, South Korea has had experience in producing major defense systems, especially fighter jets. Map rivalry jet fighter in the world in recent years is very fierce. South Korea in 2010 running the KFX fighter jet development program. Indonesia in the era of President SBY began to modernize its defense system's main tool. South Korea eventually invites Indonesia to join the program. On July 15, 2010, Indonesia has officially joined the KFX/IFX fighter jet project, through the signing of a memorandum of understanding (MoU). This study aims to find out, what were the factors that affect South Korea chose Indonesia to be a partner in the project development of fighter jets KFX / IFX. Keywords: KFX / IFX, South Korea, Indonesia, fighter jets, major defense system